Beyond the Enclave: Towards a Critical Political Economy of China and Africa. Issue 6 (4th November 2013) - Mohan, Giles
ABSTRACT: This article provides a political economy framework for analysing China's engagements with Africa. It situates the rise of China in the context of the changing balance of power in the world system and particularly China's re‐entry into spheres of influence in Africa that have been the purview of the former European colonial powers for two centuries or more. It begins by arguing that current approaches to China, Africa and international relations are fragmented in particular ways which prevent the development of a more critical political economy. It then examines a pervasive theme in China–Africa relations, which assumes that the Chinese work through enclaved investments to secure the resources of low‐income economies, though in this sense the Chinese are no different from other investors. Where they do differ is in their bundling of aid, trade and FDI and their use of imported labour, which has been termed 'surgical colonialism'. The article does not dispute the existence of Chinese enclaves but argues that we need more empirical evidence on the levels of labour importation in relation to local labour market conditions. This requires a more nuanced understanding of state–capital dynamics in those countries where the Chinese operate although the model appears to be one of elite brokerage. However, the enclaved investments and inter‐elite bargaining are only part of the story and the closing sections of the article analyse the role of independent Chinese businesses in Africa's social and political development, which moves us beyond the enclave.